'A strange country': representations of the nascent state of Israel in the Turkish press. Issue 5 (3rd September 2022) - Solomonovich, Nadav
ABSTRACT: This article analyses a series of 14 articles, published in the widespread daily Turkish newspaper Yeni Sabah in June 1949 under the title 'A Strange Country: Yeni Sabah 's Correspondent Mehmet Ataker reports from Israel'. It shows that while Turkey was the first Muslim state to have recognised Israel, Yeni Sabah adopted a clear anti-Israel stance, transmitting the Palestinian narrative on the 1948 war to its Turkish readers and attempting to delegitimize Israel by questioning the idea of Jewish nationalism and using symbols and images associated with classic antisemitism to deride Israelis and Jews.